2022
DOI: 10.3389/fpubh.2022.970660
|View full text |Cite
|
Sign up to set email alerts
|

“Blood lead level among battery factory workers in low and middle-income countries: Systematic review and meta-analysis”

Abstract: IntroductionLead is one of the most health-hazardous causes of acute and chronic poisoning at workplaces. A limited study was conducted on the blood lead concentration among battery factory workers in low and middle-income countries. Therefore, this study will improve workplace health and safety conditions of workers in this sector and serve as baseline data for further studies in this segment of the working setup.ObjectiveThis review aims to identify the pooled mean blood lead level among battery factory work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…A systematic review and meta-analysis of BLLs in battery factories' workers in these countries showed an average level of 37.9 μg/dL, with the highest level in Bangladesh (65.2 μg/dL), followed by Pakistan (60.4 μg/dL) and Egypt (52.4 μg/dL). 24 Haryanto 25 reports that there are more than 200 battery recycling smelters in Indonesia, 71 of which are located in Jakarta. The average BLLs for non-smelter workers was higher in 2015 (>39.3 μg/ dL) than in 2011 (27.9 μg/dL), and people living near smelters are at risk of Pb poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis of BLLs in battery factories' workers in these countries showed an average level of 37.9 μg/dL, with the highest level in Bangladesh (65.2 μg/dL), followed by Pakistan (60.4 μg/dL) and Egypt (52.4 μg/dL). 24 Haryanto 25 reports that there are more than 200 battery recycling smelters in Indonesia, 71 of which are located in Jakarta. The average BLLs for non-smelter workers was higher in 2015 (>39.3 μg/ dL) than in 2011 (27.9 μg/dL), and people living near smelters are at risk of Pb poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…Oleh karena itu, perhatian harus diberikan oleh pengusaha, pemerintah, dan peneliti untuk meningkatkan kesehatan populasi pekerja yang terpapar timbal di negara-negara berpenghasilan rendah dan menengah melalui penyediaan layanan kesehatan dan keselamatan kerja seperti pemeriksaan kesehatan berkala, perawatan, dan penyediaan layanan kesehatan. pelatihan dan peralatan pelindung diri yang memadai dan sesuai 26 . Kadar timbal dalam darah lebih dari 40 𝜇g/dl, akan memberikan efek toksik yang berdampak hampir ke semua organ.…”
Section: Hasil Dan Pembahasanunclassified
“…If an article has less than 60% 'yes' responses, it is defined as a low-quality study and will be excluded. This criterion has been also utilised in previous studies (Boehm et al, 2021;Zhang et al, 2023).…”
Section: Quality Appraisalmentioning
confidence: 99%